Sprint acceleration technique is associated with lower limb injury epidemiology in professional male Rugby Union players: a seven-season analysis - Wild, J. J.; Bezodis, N. E. (Journal of Science and Medicine in Sport, 2026)
Objectives To investigate whether sprint acceleration technique is associated with the epidemiology of non-contact lower limb running-based injuries in professional male Rugby Union players. Design Retrospective analysis of prospectively collected cohort data. Methods Eighty-five professional male rugby players were monitored across seven seasons, comprising 63,786 total hours of training and match exposure. Players were classified into four sprint acceleration strategy groups based on their spatiotemporal characteristics obtained during quantitative sprint acceleration testing. Non-contact lower limb running-based injuries were prospectively recorded using standardised injury surveillance methods. Injury incidence, severity, and burden were calculated per 1000 player hours. Poisson regression models were used to determine relative risks for index injuries by acceleration strategy group, adjusting for exposure and age. Results Sixty-two players sustained 123 non-contact lower limb running-based injuries. Calf injuries had the highest incidence, whilst hamstring injuries imposed the greatest burden. Players adopting a high step-rate and short flight time strategy were over 2.5 times more likely to sustain hamstring injuries, whereas those adopting a longer step length and longer flight time strategy were over 2.5 times more likely to sustain calf injuries. Conversely, the high step-rate and short flight time strategy was associated with a substantially lower risk of calf injury. Conclusions Sprint acceleration technique is associated with site-specific non-contact lower limb injury risk in professional male rugby players. Acceleration strategy-specific injury profiles highlight the importance of incorporating individual sprint mechanics into multifactorial injury prevention and monitoring practices.